STRUCTURE AND SUCCESSION OF ALPINE PERENNIAL COMMUNITY (POLYGONUM CUSPIDATUM) ON MT. FUJI (Twelfth Symposium on Polar Biology) - マスザワ, タケヒロ; スズキ, ジュンイチロウ; MASUZAWA, Takehiro; SUZUKI, Jun-ichirou (National Institute of Polar Research, 1991)
P(論文) Successional process of herbaceous perennial was investigated on the alpine zone of Mt. Fuji. The study site is located at the timberline of the southeast slope where it is mainly covered by various growing types of Polygonum cuspidatum patch. The structure of these patches was studied in relation to the successional stage of the alpine timberline. Measurements of shoot height, density of shoots, biomass above the ground and soil nutrient condition were carried out in patches of various sizes. The biomass of large, medium and small patches was 3400, 970 and 120g, respectively. In the central part of the large patch, a low density and low biomass area (dead center) existed, and where other species have invaded. These various-sized patches play a significant role in the successional process on the alpine zone. departmental bulletin paper